2023
DOI: 10.3390/molecules28020575
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Catechins from Green Tea Waste in Single- and Double-Layer Liposomes via Their Incorporation into a Functional Green Kiwifruit Juice

Abstract: Globally, about one million tonnes of tea products, which contain high concentrations of catechins and their derivatives, are wasted annually. Therefore, green tea waste catechins (GTWCs) are worth extracting, processing, protection, and delivery to the human body. In this study, GTWCs were extracted using a green method and then encapsulated in both single- (SLLs) and double-layer liposomes (DLLs). The encapsulated extracts were subsequently incorporated into a fresh green kiwifruit juice. SLLs and DLLs conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The zeta potential of the encapsulated E. intermedia extract was found to be 33 mV, while the same parameter was reported to be 12 mV for the liposomal extract of green tea [97] . Other studies reported zeta potentials of 67 mV and 6.16 mV for the same plant extract [98] . The reasons for the difference in zeta potential depend on the types of nanostructures used in the production of nanocarriers [99] .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The zeta potential of the encapsulated E. intermedia extract was found to be 33 mV, while the same parameter was reported to be 12 mV for the liposomal extract of green tea [97] . Other studies reported zeta potentials of 67 mV and 6.16 mV for the same plant extract [98] . The reasons for the difference in zeta potential depend on the types of nanostructures used in the production of nanocarriers [99] .…”
Section: Resultsmentioning
confidence: 79%
“…[97] Other studies reported zeta potentials of 67 mV and 6.16 mV for the same plant extract. [98] The reasons for the difference in zeta potential depend on the types of nanostructures used in the production of nanocarriers. [99] A nanocarrier, e. g., poly(methyl methacrylate) (PMMA) refers to a type of distinct delivery system used in a variety of medicinaland biotechnological-based disciplines to transport drugs, genetic material, or other substances at the nanoscale level.…”
Section: Investigation Of Particle Size and Zeta Potential Of Synthet...mentioning
confidence: 99%